Effect of potassium on chemical composition, uptake and soil properties of groundnut (Arachis hypogaea L.) grown in loamy sand soil: EFFECT OF POTASSIUM ON GROUNDNUT YIELD - S K SHAH; P B CHAUDHARI; K V CHAUDHARY; S F CHAUDHARY; A G DESAI (Journal of Oilseeds Research, 2021)
A field experiment was carried out at Castor Mustard Research Station, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar (Gujarat) India in summer season to study the effect of potassium on chemical composition, uptake and soil properties of groundnut (Arachis hypogaea) grown in loamy sand soil. The soil of experimental site was low in organic carbon (0.2%); EC (0.1 /dSm) and available N (155.6 kg/ha); medium in available P2O5 (44.2 kg/ha) and available K2O (256.1 kg/ha) with neutral soil pH of 7.2. The experiment was framed with ten treatments namely T1: RDF (25:50:00 kg/ha), T2 : RDF + KSB, T3 : RDF + 20 kg K2O, T4 : RDF + 40 kg K2O, T5 : RDF + 15 kg K2O + KSB, T6 : RDF + 30 kg K2O + KSB, T7 : 75 % RDF + NPK consortium, T8 : NPK consortium, T9 : RDF + NPK consortium and T10 : Absolute Control in randomised block design with three replications using groundnut variety GG 2. The significantly higher seed yield of 2872 kg/ha was recorded in treatment T9. The N, P and K content and uptake was found maximum in treatment T9 (RDF + NPK consortium). Significantly the higher values of available N (184.5 kg/ha), P2O5 (51.4 kg/ ha) and K2O (260.7 kg/ha) content in soil after harvest of crop was recorded with the treatment T9 . Except T1 , T8 and T10 all treatments recorded the highest value of soil organic carbon (0.3%). The maximum potassium use efficiency was noted under treatment T5 (RDF + 15 kg K2O + KSB) (28.9 kg/ha). The maximum bacterial, fungul and actinomycets population was noted under treatment T9 [RDF (25:50:00 kg/ha) + NPK consortium].